1989
DOI: 10.3758/bf03329891
|View full text |Cite
|
Sign up to set email alerts
|

Visual asymmetry biases assessment of conjugate lateral eye movement

Abstract: This paper reports a serendipitous observation. Prior research led to the expectation that equal numbers of right-movers and left-movers would be found in a study aimed at exploring individual differences in conjugate lateral eye movement. Instead, most subjects were found to be right-movers (p < .001). Scrutiny ofthe study's procedures revealed that the subjects had inadvertently been placed next to the left wall of the room. Apparently asymmetrical visual stimulation during the assessment of conjugate latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, many different influences can affect looking behavior. For example, Baker (1989) demonstrated that visual asymmetry influenced direction of gaze, with participants consistently making eye movements away from the closest wall in the room. Rodin and Singer (1976) found that even if people predominately look to the right, they will stop doing so if another person is standing there.…”
Section: Discussionmentioning
confidence: 99%
“…However, many different influences can affect looking behavior. For example, Baker (1989) demonstrated that visual asymmetry influenced direction of gaze, with participants consistently making eye movements away from the closest wall in the room. Rodin and Singer (1976) found that even if people predominately look to the right, they will stop doing so if another person is standing there.…”
Section: Discussionmentioning
confidence: 99%